Language Performance of Iraqi Patients with Stroke: A Case Study. - Ahmed Hashim (مجلة اداب ذي قار)
This paper deals with the language performance of Iraqi patients suffering from stroke. It defines what is meant by stroke, exhibits stroke types, and discusses aphasia disorder that is resulted from stroke in the left hemisphere of the brain. The researcher takes a case of three stroke patients who live in Dhi Qar province for this study and communicates with them to find which language areas are affected and what difficulties the patients face due to their brain injury. Since language is located on the left hemisphere of the brain, the selection of the case is limited to those who suffer from stroke in their left hemisphere where language areas are located.